The Labyrinth of Osiris - Sussman, Paul (London Bantam Books, 2013)
Detective Arieh-Ben Roi of the Jerusalem police investigates the murder of a well-known Israeli journalist and discovers a connection to the mysterious death of a 1930s Egyptologist, who had claimed to have uncovered a labyrinth of unfathomable treasures.
Keywords: Egypt -- Journalists -- Murder--Investigation